Parecoxib has non-significant long-term effects on bone healing in rats when administered for a short period after fracture - Akritopoulos, Panagiotis (Springer-Verlag, 2008)
INTRODUCTION: Selective and non-selective cyclo-oxygenase (COX) inhibitors impair bone healing by inhibiting prostaglandin synthesis. The purpose of this study was to evaluate the long-term effect of parecoxib, a selective COX-2 inhibitor, on bone healing in rats, when it is applied in a pattern similar to clinical treatment patterns, that is, in a high dose and for a short period after bone fracture. METHOD: Closed non-displaced mid-diaphyseal fractures in the middle of the left femoral shaft were generated in each animal. In the study group, parecoxib sodium (1.06 mg/kg) was administered intra-peritoneally every day for 7 days. In the control group, normal saline was administered intra-peritoneally every day for 7 days. In both groups fracture healing (bone union and callus formation) was evaluated with X-rays 28 and 42 days after surgery. RESULTS: Bone healing was lower in the study group (60 vs. 80% in the control group 28 days after fracture and 80 vs. 90% 42 days after fracture) but this difference was not statistically significant (P > 0.05). CONCLUSION: Parecoxib does not have a significant long-term effect on bone healing in rats, when it is administered in a high dose and for a short period after bone fracture.